Association between walking speed and cognitive domain functions in Chinese suburban-dwelling older adults - Wang, Hong; Zhang, Hui; Chen, Yaoxin; Cai, Ming; Guo, Cailian; Chen, Peijie (Frontiers in Aging Neuroscience, 2022)
Objective To examine the relationship among walking speed, cognitive impairment, and cognitive domain functions in older men and women living in a Chinese suburban community. Methods In total, 625 elderly (72.54 ± 5.80 years old) men (n = 258) and women (n = 367) from the Chongming district of Shanghai participated in this study. All participants had Mini-Mental State Examination (MMSE), 4-m walking test, medical history questionnaire, and physical examination. They were grouped according to walking speed (>0.8 vs. ≤ 0.8 m/s) with the stratification of sex. The odds ratio (OR) and the 95% confidence interval (CI) were assessed using the chi-square test and logistic regression analysis. Results Around 11.6% of men and 14.2% of women had slow walking speeds. After adjusting for age, body mass index (BMI), education level, spouse, faller, the Geriatric Depression Scale (GDS) score, heart disease, stroke, arthritis, and low back pain, walking speed was negatively related to cognitive impairment in men (OR 0.11 [95% CI: 0.01, 0.94]; p = 0.043). In addition, the relationship between walking speed and impaired orientation was significant in both men (OR 0.003 [95% CI: 0.001, 0.05]; p < 0.001) and women (OR 0.15 [95% CI: 0.03, 0.75]; p = 0.021). Conclusion The relationship between walking speed and cognitive impairment was only significant in men, but the association with impaired orientation was found in both men and women. Assessing the walking speed of the elderly is beneficial, which may help with early detection and early therapeutic prevention of cognitive impairment.